Systems bioinformatics [ an engineering case-based approach - Alterovitz, Gil; Ramoni, Marco F. (Artech House bioinformatics & biomedical imaging series, 2007)
Gives engineers a quantitative systems approach to bioinformatics research using computational tools drawn from technical disciplines.